Inisiasi pengelolaan alarm fatigue perawat melalui panduan manajemen alarm di ruang intensif - Widyaningsih, Neni; Handiyani, Hanny; Pujasari, Hening; Masfuri, Masfuri (Holistik Jurnal Kesehatan, 2025)
Background: Alarm fatigue in nurses working in intensive care units is still a critical issue and priority in patient safety. Alarm fatigue is a condition when someone becomes insensitive to safety warnings due to receiving too many alarms. Alarm fatigue can be prevented by implementing effective alarm management. On the other hand, the current implementation of alarm management is still not optimal. Head nurses play an important role in efforts to prevent alarm fatigue incidents and oversee the implementation of alarm management and need direction in its implementation in intensive care units. Purpose: To initiate alarm fatigue management for nurses through alarm management guidelines in intensive care units. Method: A case report study according to Kotter's planned change stages was conducted at the University of Indonesia Teaching Hospital on April 22 - May 24, 2024. The research process included assessment, data analysis, action plan (PoA), implementation, and evaluation. Data collection was carried out through interviews, observations, and filling out questionnaires. Results: The priority problems obtained were the suboptimal planning function related to alarm fatigue management through alarm management and implementation through Kotter's theory which had only been carried out until the third stage. Conclusion: Planned changes can be made in the implementation of implementation in solving problems. The problem found was the suboptimal function of the head of the room in alarm management in the intensive care unit. The alarm management guide that has been created is expected to prevent the occurrence of fatigue alarms in nurses and provide quality services. Suggestion: The draft guide for managing nurse fatigue alarms through alarm management can be approved by the president director and applied in services in the hospital's intensive care unit. In addition, the hospital can organize training and education for nursing staff to improve understanding of fatigue alarms, effective alarm management, and conduct periodic evaluations.   Keywords: Alarm Management; Fatigue Alarm; Intensive Care Unit; Nurses.   Pendahuluan: Alarm fatigue pada perawat yang bekerja pada ruang intensif masih menjadi masalah yang kritis dan prioritas dalam keselamatan pasien. Alarm fatigue adalah kondisi ketika seseorang menjadi tidak peka terhadap peringatan keselamatan akibat menerima terlalu banyak alarm. Alarm fatigue dapat dicegah dengan menerapkan manajemen alarm yang efektif. Di sisi lain, penerapan manajemen alarm saat ini masih belum optimal. Head nurse memainkan peran penting dalam upaya mencegah kejadian alarm fatigue dan mengawasi pelaksanaan manajemen alarm dan membutuhkan panduan dalam pelaksanaannya di ruang intensif. Tujuan: Untuk menginisiasi pengelolaan alarm fatigue perawat melalui panduan manajemen alarm di ruang intensif. Metode: Penelitian case report sesuai tahapan perubahan terencana Kotter’s, dilakukan di Rumah Sakit Pendidikan, Universitas Indonesia pada tanggal 22 April – 24 Mei 2024. Proses penelitian meliputi pengkajian, analisis data, rencana tindakan/plan of action (PoA), implementasi, dan evaluasi. Data dikumpulkan melalui wawancara, observasi, dan pengisian kuesioner. Hasil: Prioritas masalah yang didapat yaitu fungsi perencanaan belum optimal terkait dengan pengelolaan alarm fatigue melalui manajemen alarm dan implementasi melalui teori Kotters, dilakukan baru sampai pada tahap yang ketiga. Simpulan: Perubahan terencana dapat dilakukan dalam pelaksanaan implementasi dalam menyelesaikan masalah. Permasalahan yang ditemukan yakni belum optimalnya fungsi perencanaan kepala ruangan dalam manajemen alarm di ruang intensif. Panduan manajemen alarm yang telah dibuat diharapkan dapat mencegah terjadinya alarm fatigue pada perawat dan memberikan pelayanan yang berkualitas. Saran: Draft pengelolaan alarm fatigue perawat melalui manajemen alarm dapat disahkan oleh direktur utama dan diterapkan dalam pelayanan di ruang intensif rumah sakit. Selain itu, pihak rumah sakit dapat menyelenggarakan pelatihan dan edukasi bagi staf perawat untuk meningkatkan pemahaman tentang alarm fatigue, manajemen alarm yang efektif, dan melakukan evaluasi secara berkala.   Kata Kunci: Alarm Fatigue; Manajemen Alarm; Perawat; Ruang Intensif.